2020
DOI: 10.21315/mjms2020.27.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Farming Activities and Plasmodium falciparum Transmission in Rural Communities in Nigeria

Abstract: Background The connection between malaria-associated morbidities and farming activities has not been succinctly reported. This study aimed to address the connectivity between farming activities and malaria transmission. Methods The study took place in the agricultural setting of Nigeria Edu local government (9° N, 4.9° E) between March 2016 and December 2018. A pre-tested structured questionnaire was administered to obtain information on their occupation and malaria inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The very high abundance of Anopheles larvae in paddy (rice field) is presumably due to the early stage of rice growth and heavy rainfall during the survey which agrees with previous findings other researchers who reported that early stages of rice growth have been associated with high densities of mosquito larvae [9][10][11][12][13].Larval counts and density of Anopheles mosquitoes are known to be high during rainy seasons and decline at dry seasons [14]. Studies have shown similar trends where greater assemblages of anopheline species were associated with villages in rice growing which had permanent and diverse larval habitats [15].…”
Section: Habitat Types Utilized By Anopheles Mosquitoes For Breeding ...supporting
confidence: 91%
“…The very high abundance of Anopheles larvae in paddy (rice field) is presumably due to the early stage of rice growth and heavy rainfall during the survey which agrees with previous findings other researchers who reported that early stages of rice growth have been associated with high densities of mosquito larvae [9][10][11][12][13].Larval counts and density of Anopheles mosquitoes are known to be high during rainy seasons and decline at dry seasons [14]. Studies have shown similar trends where greater assemblages of anopheline species were associated with villages in rice growing which had permanent and diverse larval habitats [15].…”
Section: Habitat Types Utilized By Anopheles Mosquitoes For Breeding ...supporting
confidence: 91%
“…Our search yielded 2913 studies after removal of duplicates ( figure 1 ). 53 studies 8 , 24 , 25 , 26 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 (with a total of 113 160 participants) met the inclusion criteria, various subsets of which were included in the quantitative, semi-quantitative, and qualitative analyses depending on the outcome of interest (appendix pp 2–7). 23 (43%) studies reported data on parasite prevalence, five (9%) on malaria incidence, 36 (68%) on human biting rate, 22 (42%) on sporozoite rate, and 19 (36%) on entomological inoculation rate.…”
Section: Resultsmentioning
confidence: 99%
“…22 studies reported malaria prevalence in rice-growing and non-rice-growing villages and were included in the meta-analysis, with 16 studies 26 , 27 , 29 , 30 , 32 , 33 , 37 , 38 , 39 , 40 , 43 , 47 , 49 , 52 , 55 , 58 conducted before 2003 and seven studies 58 , 64 , 66 , 70 , 73 , 74 , 75 since 2003 (one study included analyses both before and since 2003; figure 2 A). Before 2003, rice-growing was not associated with increased malaria prevalence (crude RR 0·82 [95% CI 0·63–1·06], 16 studies, 99 574 participants; adjusted OR [aOR] 0·73 [95% CI 0·57–0·89], two studies, 11 955 participants; appendix p 8).…”
Section: Resultsmentioning
confidence: 99%
“…While little documentation exists regarding the presence of P. vivax in Oman beyond the early 1900s, there is evidence of agriculture in some regions of Oman dating back to the first millennium AD 90 . Agriculture has been linked to malaria transmission in several countries [91][92][93] , and P. vivax may have been present in Oman by the time Fy ES was introduced. Whether this could have driven strong selection, however, is unclear.…”
Section: Discussionmentioning
confidence: 99%